Kontribusi Lingkungan dan Pembelajaran Wirausaha dalam Menumbuhkan Minat Berwirausaha - A Rony Yulianto (Universitas Pancasakti Tegal, 2021)
The study aims to determine the influence of the family environment, social environment and entrepreneurial learning on entrepreneurial interests. The subjects of this study were 54 class XII students of SMK PGRI Tegal, who were taken incidentally. The results showed that partially the family environment, social environment and entrepreneurial learning influenced the interest in entrepreneurship. Furthermore, it simultaneously shows the social environment and entrepreneurial learning influences the interest in entrepreneurship, while the family environment does not show a positive influence. Entrepreneurial learning has the most dominant influence in growing entrepreneurial interest for students. This research has implications for improving the quality of entrepreneurial learning in schools, in order to be able to foster student interest in entrepreneurship.